Elements of forensic description of threats or violence against a law enforcement officer - I. P. Fedorishchev (Bulletin of Kharkiv National University of Internal Affairs)
Proper legal regulation of the protection of law enforcement officers from unlawful attacks should be one of the most important tasks of a developed state governed by the rule of law, especially in the context of active hostilities, because even in peacetime law enforcement officers put their health and lives at risk. At the same time, state institutions must provide adequate guarantees to ensure the normal functioning of the law enforcement system.